2021
DOI: 10.15252/msb.202010188
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection remodels the host protein thermal stability landscape

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global threat to human health and has compromised economic stability. In addition to the development of an effective vaccine, it is imperative to understand how SARS-CoV-2 hijacks host cellular machineries on a system-wide scale so that potential host-directed therapies can be developed. In situ proteome-wide abundance and thermal stability measurements using thermal proteome profiling (TPP) can inform on global changes in protein activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In studies by Joel Selkrig et al [126] attempts were made to disturb the SARS-CoV-2induced destabilization of HSP90 by the use of tanespimycin-an HSP90 inhibitor. The resulting inhibition of viral proliferation provided convincing evidence that SARS-CoV-2 requires the presence of HSP90 for proliferation during infection.…”
Section: Influenza a Virus (Iav)mentioning
confidence: 99%
“…In studies by Joel Selkrig et al [126] attempts were made to disturb the SARS-CoV-2induced destabilization of HSP90 by the use of tanespimycin-an HSP90 inhibitor. The resulting inhibition of viral proliferation provided convincing evidence that SARS-CoV-2 requires the presence of HSP90 for proliferation during infection.…”
Section: Influenza a Virus (Iav)mentioning
confidence: 99%
“…One new technique to probe the RNA-protein and protein-protein interactions as a function of temperature is thermal proteome profiling (TPP). It can reveal molecular interaction networks and the stability of the interactions in these networks ( 130 ) and can be used to study which links in the interaction network change upon RNA virus infections or between different infections ( 131 ). For instance, TPP revealed that during SARS-CoV-2 infection, the virus induces changes in the cell cycle and microtubule and spliceosome complexes ( 131 ), highlighting the role of endogenous host protein machinery being utilized by the virus for its survival.…”
Section: Tools To Study the Effect Of Temperature On Rna Viruses And ...mentioning
confidence: 99%
“…48 An MS-based approach defined phosphoribosylated peptides alongside phosphopeptides on distinct proteoforms in lipopolysaccharide (LPS)-stimulated macrophages, pointing to possible functional cross-talk between PTMs. 49 Thermal proximity coaggregation (TPCA) and thermal proteome profiling have characterized overall impacts, both pro-and antiviral, on protein−protein interactions of human cytomegalovirus, 50 SARS-CoV-2, 51 and herpes simplex virus type 1. 52 The TPCA method captured dynamic enzyme−substrate interactions, leading to discovery of a functional link between the viral DNA interferon inducible protein 16 (IFI16) and the DNA-dependent protein kinase (DNA-PK), 52 enhanced computationally.…”
Section: Post-translational Modifications (Ptms) In Infectious Diseasesmentioning
confidence: 99%